Performance Standards’: Utility for Different Uses of Assessments - Linn, Robert L. (Education Policy Analysis Archives, 2003)
Performance standards are arguably one of the most controversial topics in educational measurement. There are uses of assessments such as licensure and certification where performance standards are essential. There are many other uses, however, where performance standards have been mandated or become the preferred method of reporting assessment results where the standards are not essential to the use. Distinctions between essential and nonessential uses of performance standards are discussed. It is argued that the insistence on reporting in terms of performance standards in situations where they are not essential has been more harmful than helpful. Variability in the definitions of proficient academic achievement by states for purposes of the No Child Left Behind Act of 2001 is discussed and it is argued that the variability is so great that characterizing achievement is meaningless. Illustrations of the great uncertainty in standards are provided.